2023
DOI: 10.3390/en16114306
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Crude Oil Prices and Renewable Energy Production: Evidence from the USA

Abstract: This study aims to examine the short-term and long-term relationship between WTI oil prices and renewable energy production considering U.S. crude oil production, world oil prices, and other domestic and global factors. We employ several time-series analysis techniques, including the augmented Dickey-Fuller test and the Phillips-Perron test for unit roots; the long-term relationship is examined using fully modified OLS (FMOLS) and Park’s canonical cointegration regression (CCR). We also utilise an error correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…), usually paid by the end customer. Sorokin et al [45] also explored the relationship between crude oil prices and renewable energy production, among other variables. Their various statistical approaches concluded that when crude oil production continues to be constant, evidence supports the estimation that an upsurge in energy generation from renewable sources leads to a rise in oil prices.…”
Section: State Of the Artmentioning
confidence: 99%
“…), usually paid by the end customer. Sorokin et al [45] also explored the relationship between crude oil prices and renewable energy production, among other variables. Their various statistical approaches concluded that when crude oil production continues to be constant, evidence supports the estimation that an upsurge in energy generation from renewable sources leads to a rise in oil prices.…”
Section: State Of the Artmentioning
confidence: 99%